The incorporated aortomitral homograft for double-valve endocarditis: the 'hemi-Commando' procedure. Early and mid-term outcomes. (15th December 2017) - Elgharably, Haytham; Hakim, Ali H; Unai, Shinya; Hussain, Syed T; Shrestha, Nabin K; Gordon, Steven; Rodrıguez, Leonardo; Gillinov, A Marc; Svensson, Lars G; Navia, José L
Abstract: OBJECTIVES: Surgical management of invasive double-valve infective endocarditis (IE) involving the intervalvular fibrosa (IVF) is a technical challenge that requires extensive debridement followed by complex reconstruction. In this study, we present the early and mid-term outcomes of the hemi-Commando procedure and aortic root replacement with reconstruction of IVF using an aortomitral allograft. METHODS: From 2010 to 2017, 37 patients with IE involving the IVF underwent the hemi-Commando procedure. Postoperative clinical data and echocardiograms were reviewed for the assessment of cardiac structural integrity and clinical outcomes. RESULTS: Twenty-nine (78%) cases were redo surgery and 15 (41%) were emergency surgery. Preoperatively, 70% ( n = 26) of patients were admitted to the intensive care unit and 11% ( n = 4) of patients were in septic shock. Ten (27%) patients had native aortic valve IE, while 27 (73%) patients had prosthetic valve IE. Hospital death occurred in 8% ( n = 3) of patients due to multisystem organ failure. Postoperative echocardiogram showed no aortic regurgitation in 86% ( n = 32) and mild regurgitation in 14% (n = 5) of patients, while mitral regurgitation prevalence was none/trivial in 62% (n = 23), mild in 32% ( n = 12) and moderate in 5%. Intact IVF reconstruction was confirmed in all patients with no abnormal communication between the left heart chambers. One-year survival was 91%, while 3-year survival was 82%. Mid-term follow up revealed 1 death secondary to recurrent IE. CONCLUSIONS: Compared to double-valve replacement with IVF reconstruction ('Commando operation'), the early and mid-term outcomes of the hemi-Commando procedure proved to be a feasible treatment option for IVF reconstruction, enabling preservation of the mitral valve and the subvalvular apparatus in high-risk patients with invasive double-valve IE.